(untitled) (Sains Humanika, 2015)
Job satisfaction is predicted to influence employee’s decision, behavior and productivity in the organisation. Previous studies had shown a significant relationship between job satisfaction and employees’ satisfaction. The purpose of this study is to investigate the impact of Personality Big Five dimensions, self-efficacy and autonomy on job satisfaction. The review will explain the influence of self-efficacy between Personality Big Five and job satisfaction and the link of autonomy between self-efficacy and job satisfaction mostly on employees’ satisfaction.